Empowering health: exploring the vital role of facilitator organisations in supporting chronic disease patients in Assam, India - Hiranmoyee Bhuyan; Seema S. Singha (Research in Health Services & Regions)
Abstract Background The research centers on an underrated type of mediator organization namely facilitator organizations (FO) that work in the health care setting. These organizations are mediators that bridge the gap between patients (healthcare customers) and medical services. The facilitator organizations considered for the study are non-governmental organizations situated in Assam that works in align to chronic diseases, particularly cancer. Methods The data collection was done through organizational referrals for the study making it a snowball sampling, progressively incorporating additional contemporary entities. The study's respondents were facilitator organizations (i.e.Non-Government Organizations) actively involved in addressing chronic disease. Data were gathered from these facilitator organizations situated in Assam, India, supporting healthcare customers specifically those with cancer. Key informant interviews and semi-structured questionnaires were used for data collection, the responses were documented using a field diary and the Lovelock service model was used as a reference for the construction of the questionnaire and developing the research framework. Results The analysis of data shows that facilitator organisations maintain continuity in relationships, which enhances health management and outcomes for customers. The shift in cancer care towards a patient-centred approach and the crucial role of FOs in providing comprehensive and individualized care, addressing diverse patient needs thereby addressing the holistic development of the health care customer is vital. In addition, effective patient-centred communication, incorporating trust, compassion, respect and comprehensive support including mental health therapy, occupational therapy, and rehabilitation plays a crucial role in leading a normal life. ` Conclusion The facilitator organizations dealing with Cancer have to meet a broad range of services outside the core medical service providers for their healthcare customers. These efforts contribute to the overall recovery of both the healthcare customer with cancer and their family.